2010
DOI: 10.1186/1743-422x-7-76
|View full text |Cite
|
Sign up to set email alerts
|

Identification of super-infected Aedes triseriatus mosquitoes collected as eggs from the field and partial characterization of the infecting La Crosse viruses

Abstract: BackgroundLa Crosse virus (LACV) is a pathogenic arbovirus that is transovarially transmitted by Aedes triseriatus mosquitoes and overwinters in diapausing eggs. However, previous models predicted transovarial transmission (TOT) to be insufficient to maintain LACV in nature.ResultsTo investigate this issue, we reared mosquitoes from field-collected eggs and assayed adults individually for LACV antigen, viral RNA by RT-PCR, and infectious virus. The mosquitoes had three distinct infection phenotypes: 1) super i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Although this review only will address peroral transmission from a vector to a vertebrate, other modes of transmission exist, e.g., vertical transmission, both transovarial (TOT; virus in egg; [21] and vertical (virus on surface of egg as for certain flaviviruses; [22]), co-feeding transmission from an infected arthropod to uninfected arthropods feeding in close proximity and without evidence of a substantial viremia in the host [23], first noted with tick-borne pathogens [24], and non-biologic transmission such as by mechanical transmission, as with Rift Valley Fever virus [25]. Peroral transmission, as with other aspects of vector competence, is virus- and vector species-specific (see references for infection differences).…”
Section: Vector Competencementioning
confidence: 99%
“…Although this review only will address peroral transmission from a vector to a vertebrate, other modes of transmission exist, e.g., vertical transmission, both transovarial (TOT; virus in egg; [21] and vertical (virus on surface of egg as for certain flaviviruses; [22]), co-feeding transmission from an infected arthropod to uninfected arthropods feeding in close proximity and without evidence of a substantial viremia in the host [23], first noted with tick-borne pathogens [24], and non-biologic transmission such as by mechanical transmission, as with Rift Valley Fever virus [25]. Peroral transmission, as with other aspects of vector competence, is virus- and vector species-specific (see references for infection differences).…”
Section: Vector Competencementioning
confidence: 99%
“…aegypti eggs may produce infected adult mosquitoes (Khin and Than 1983 ). Arboviruses have also been found in field-collected mosquito larva that has been reared to adult stage (Dhileepan et al 1996 , Reese et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, only one study from Australia has suggested vertical transmission of SINV and the related Ross River virus, family Togaviridae , genus Alphavirus (Dhileepan et al 1996 ). INKV has not been studied regarding vertical transmission, but the La Crosse virus (family Bunyaviridae , genus Orthobunyaviridae ) in the California serogroup has been found in field collected larvae and mosquito eggs in North America (Reese et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…triseriatus , which plays a key role in amplification and maintenance of the virus by producing large numbers of LACV infected progeny and eggs in which the virus may overwinter to emerge in the spring [ 52 , 55 ]. Rates of TOT and filial infection can exceed 70%, although infection rates in field-collected materials are often significantly lower [ 56 , 57 ]. LACV is also transmitted horizontally from infected Ae.…”
Section: Selected Medically Important Bunyavirusesmentioning
confidence: 99%